2019
DOI: 10.1177/1420326x19878586
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation online monitoring and control system from the perspectives of technology application

Abstract: Dynamic optimal airflow ventilation can have a great impact on the indoor air distribution and pollutant removal to improve the indoor air quality while saving energy. An online monitoring and control ventilation system has been developed and evaluated using fast prediction models and micro-control. An environmental chamber (1.8 m3) was used for the evaluation to monitor the CO2 dispersion under different air change rates and air speed. Specifically, an artificial neural network model based on a low-dimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 42 publications
0
32
0
1
Order By: Relevance
“…(1) The deviation errors between the prediction results of linear humidity model (LHM) and CFD results were less than 15%. Considering the well-behaved linear models (i.e., LVM's error less than 13% and LTM's error less than 20%) proposed in our previous work (Cao and Ren 2018;Ren and Cao 2019a;Zhu et al 2020), the adoption of linear models could show favorable performance in the rapid prediction of indoor environmental fields. (2) The well-behaved CRI (H) model was utilized to rapidly predict indoor humidity, and the maximum prediction error compared to CFD results was less than 15%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) The deviation errors between the prediction results of linear humidity model (LHM) and CFD results were less than 15%. Considering the well-behaved linear models (i.e., LVM's error less than 13% and LTM's error less than 20%) proposed in our previous work (Cao and Ren 2018;Ren and Cao 2019a;Zhu et al 2020), the adoption of linear models could show favorable performance in the rapid prediction of indoor environmental fields. (2) The well-behaved CRI (H) model was utilized to rapidly predict indoor humidity, and the maximum prediction error compared to CFD results was less than 15%.…”
Section: Resultsmentioning
confidence: 99%
“…(3) The design of the actual control system for temperature and humidity has not been implemented in this work. According to our previous work, the ventilation rate was adjusted corresponding to the variation of fan voltage (Zhu et al 2020;Ren and Cao 2020). Thus, we can also adjust the compressor speed (i.e., compressor input voltage) of HVAC system to obtain different inlet temperature and humidity, in order to achieve the effective regulation of integrate air conditioning system (Zhong et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…53 On the basis of the ideal ‘ventilation space’, a range of ventilation technologies, such as demand-oriented ventilation, variable air volume ventilation, personalized ventilation, displacement ventilation, diffuse ceiling ventilation and optimized system sensing, monitoring and controlling technologies and data analytics can more effectively control ‘energy-saving’ and ‘healthy’ underground space environment under different scenarios. 11,15,5457…”
Section: Discussionmentioning
confidence: 99%
“…Besides appropriate design, another issue encountered in practice is to find an online control strategy that can provide a satisfactory indoor environment with high energy performance. 45,46 For instance, Wang et al. 47 found that the total energy use of a variable air volume (VAV) air-conditioning system can be reduced by 3.3% through online optimizing outdoor air ventilation.…”
Section: Discussionmentioning
confidence: 99%